Dancing the Illustrations: Development of Vernacular Notation System for Malay Dance - Leng, Poh Gee; Aboo Backer, Mumtaz Begum (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
The use of vernacular dance notation systems that are specifically created, used and circulated among the practitioners of various local Malay dance genres have become one of the alternatives for dance documentation and preservation since the 1940s, for both the academic domain (D'Cruz, 1979; Mohd Ghouse, 1979) and general public (Ahmad Omar, 2005; Daud, 1965). This article recognizes the existence of vernacular notation systems of Malay dance that are based on three categories of illustration, namely: (1) footprint notation, (2) notation of dancers' positions, and (3) floor plan. The findings were obtained from the movement score analysis based on Labanotation, as well as from literature review and participant observation. This article seeks to fill in the gap of the development and usage of vernacular notation systems that have not been explored in the context of local dance studies and research. The article also points out the roles of vernacular notation in the current dance industry. Keywords: Dance notation, vernacular notation, Malay dance